Comparison of Methods for In-House Screening of HLA-B*57:01 to Prevent Abacavir Hypersensitivity in HIV-1 Care - De Spiegelaere, Ward; Philippé, Jan; Vervisch, Karen; Verhofstede, Chris; Malatinkova, Eva; Kiselinova, Maja; Trypsteen, Wim; Bonczkowski, Pawel; Vogelaers, Dirk; Callens, Steven; Ruelle, Jean; Kabeya, Kabamba; et al. (PLOS ONE, 2015)
Abacavir is a nucleoside reverse transcriptase inhibitor used as part of combination antiretroviral therapy in HIV-1-infected patients. Because this drug can cause a hypersensitivity reaction that is correlated with the presence of the HLA-B*57:01 allotype, screening for the presence of HLA-B*57:01 is recommended before abacavir initiation. Different genetic assays have been developed for HLA-B*57:01 screening, each with specific sensitivity, turnaround time and assay costs. Here, a new real-time PCR (qPCR) based analysis is described and compared to sequence specific primer PCR with capillary electrophoresis (SSP PCR CE) on 149 patient-derived samples, using sequence specific oligonucleotide hybridization combined with high resolution SSP PCR as gold standard. In addition to these PCR based methods, a complementary approach was developed using flow cytometry with an HLA-B17 specific monoclonal antibody as a pre-screening assay to diminish the number of samples for genetic testing. All three assays had a maximum sensitivity of >99. However, differences in specificity were recorded, i.e. 84.3%, 97.2% and >99% for flow cytometry, qPCR and SSP PCR CE respectively. Our data indicate that the most specific and sensitive of the compared methods is the SSP PCR CE. Flow cytometry pre-screening can substantially decrease the number of genetic tests for HLA-B*57:01 typing in a clinical setting.